Impact of paleosalinity, paleoredox, paleoproductivity/preservation on the organic matter enrichment in black shales from triassic turbidites of semanggol basin, peninsular malaysia - Sajid, Z. (MDPI AG, 2020)
Turbidite-associated black shale of the Semanggol Formation is extensively distributed in the northwestern part of the Western Belt, Peninsular Malaysia. The black shale occurs as a dark grey to black and thick to medium-bedded deposit. It represents the distal part of submarine fan system (outer-fan) overlying interbedded sandstone to shale facies of the mid-fan and conglomeratic pebbly sandstone facies of the inner-fan. Field observations and its widespread occurrence have resulted in the black shale being considered as a potential analog for a source rock in offshore Peninsular Malaysia. The present study includes detailed mineralogical (XRD, SEM, and EDX analysis), inorganic geochemical (major oxides, trace elements TEs, and rare earth elements REEs), and Rock-Eval pyrolysis analyses of the black shale samples, collected from the Gunung Semanggol, Bukit Merah, and Nami areas in northwestern Peninsular Malaysia. The primary focus of this study is to investigate the provenance, paleoredox conditions, paleoclimate, sedimentary rate, paleoproductivity, and upwelling system that would be helpful to understanding the role of these parameters in the enrichment of organic matter (OM) in the black shale. The Rock-Eval analysis shows that the black shale of the Semanggol Formation comprises type-III kerogens, which suggests organic input from a terrestrial source. The black shale also contains mature to postmature organic matter. Based on the mineralogical analysis, the mineral composition of the black shale comprises illite and kaolinite, with abundant traces of quartz and feldspar as well as few traces of titanium and zircon. Inorganic geochemical data designate black shale deposition in a passive margin setting that has experienced moderate to strong weathering, semi-arid to hot arid climate, and moderate sedimentation rate. Ratios of Ni/Co, U/Th, and V/(V+Ni) along with slightly negative to positive Ce* anomalies and UEF-MoEF cross-plot unanimously indicate anoxic/dysoxic water conditions that are suitable for organic matter preservation. Geochemical proxies related to modern upwelling settings (i.e., Cd/Mo, Co vs. Mn) show that the deep marine black shale was strongly influenced by persistent upwelling, a first-order controlling factor for organic matter enrichment in the distal part (outer fan of the submarine fan system) of the Semanggol Basin. However, productivity-controlled upwelling and a high sedimentary rate, as well as high-productivity in oxygen-depleted settings without strong anoxic conditions, has played an essential role in the accumulation of organic matter. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.